MODEL PENDIDIKAN KESETARAAN PAKET A SETARA SD /MI MATA PELAJARAN PPKN - Nur Hafni; Khasanah Khasanah (Akademika, 2019)
Exploration studies conducted in reality show that the implementation of equality education at the Center for Community Learning Activities (PKBM) is still not in accordance with the demands of the curriculum and National Standards for Early Childhood Education and Community Education. The purpose of this study are: 1) to find out how the steps in the preparation of equality education modules in the PPKn Package A equivalent to SD / MI, 2) Testing the effectiveness of learning by using modules in the learning process. 3) Test the validity and reliability of equality education module products in PPKn Package A courses equivalent to SD / MI. The target in this study was grade VI students at PKBM Putri Gina which consisted of one class with 15 learning residents. This study uses a sampling technique is purposive sampling that is deliberate sampling in accordance with the requirements of the composition of sample members based on the type of treatment. Based on the results of the. This is also supported by the preparation of modules that are independent and contextual so as to facilitate citizens to learn packages that have limited, time to attend teaching and learning activities can continue to follow module-based learning independently.Discussion, it was concluded that the model A education model is equivalent to SD / MI PPKn subjects. After testing, learning by using the equivalency module A package SD / MI PPKn subjects have effectiveness in the learning process